Extraction of asymptomatic impacted third molars – a review - Błochowiak, Katarzyna; Aleksandrzak, Paweł; Kropielnicki, Kacper; Handschuh, Jakub; Pawlik, Patrycja; Stanek, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. The prophylactic extraction of asymptomatic wisdom teeth is defined as the surgical removal of wisdom teeth in the absence of local disease. Early extraction of asymptomatic third molars is considered beneficial to patients to prevent the risk of future pathology, and to minimize operative and postoperative risks. The second concept is watchful monitoring of asymptomatic wisdom teeth, adhering to specific indicators for their extraction. Aim. The aim of this paper is to present and evaluate the indications and effects of prophylactic extraction of asymptomatic impacted third molars in adolescents and adults, compared with their retention and watchful monitoring. Material and methods. This study is based on analysis of literature. Conclusion. There exist clear indications for the extraction of third molars which are associated with pathology. Prophylactic extractions of asymptomatic impacted third molars should be performed only before 20 years of age. In older age, asymptomatic third molars should be retained and watchfully monitored, and removed only in cases of evident clinical or radiological symptoms.
Keywords: impaction; surgery; third molars; wisdom teeth